Formulaic Expressions for Foreign Language Learning and Teaching - Schmale, Günter (Linguistik Online, 2022)
Foreign language teaching experts unanimously insist on the necessity of acquiring formulaic expressions in order to communicate successfully in the target language. However, many of the treatises in favour of phraseme use, including semantically non-compositional idiomatic expressions, by foreign language learners seem to be marked by an insufficient depth of reflection as to applied linguistic, methodological, and phraseodidactic[1] criteria. The present contribution therefore aims at a differentiated treatment of prefabricated communicative constructions, starting out from an extended definition and classification and by discussing the pros and cons of phraseme acquisition. These considerations will lead to the delimitation of formulaic language fundamental for an operative foreign language competence (routine formulae, collocations and “constructions”) as opposed to those types of phrasemes which are not essential or even inappropriate for non-native speakers. [1] A term as a direct translation from German Phraseodidaktik, employed in English language publications of non-native researchers, e. g. Gonzalez-Rey (2018), which we decided to adopt here for practical reasons.